THE EFFECT OF CIBODAS BOTANICAL GARDEN OFFICIAL WEBSITE PUBLICITY ON DOMESTIC TOURISTS VISITING DECISIONS - Layung Paramesti Martha; Prasetyo Adinugroho; Qamila Arianti Luthfindani (UNIVERSITAS PAKUAN, 2022)
The research to identify the influence of the Cibodas Botanical Garden official website publicity on the visiting decision to domestic tourist which describe how publicity on the official website of Cibodas Botanical Garden and analyze the influence of official website publicity with visit decision of Cibodas Botanical Garden domestic tourist. The research are use one independent variable which is official website publicity and the visiting decision of domestic tourist as dependent variable. The research uses survey techniques, which means that all member of the research population were able as research respondents with a total of 100 domestic tourist Cibodas Botanical Garden. To collect the researchs data were used techniques questionnaire, observation and documentation. There were two data analyze techniques, descriptive statistics (table and percentage) and non-parametric statistics (Simple Linear Regression, F-Test, T-Test, Coefficient of Determination). The results shown that there was a significant influence between Cibodas Botanical Garden official website publicity and visiting decision to domestic tourist which are 41 percent. Then the other 59 percent are influenced by the other factor.